Heat and Mass Transfer from a Convectively Heated Vertical Surface with Chemical Reaction and Internal Heat Generation - SEINI, Ibrahim Yakubu (Engineering Transactions, 2019)
A numerical approach has been adopted to investigate the steady chemically mixed convection boundary layer flow from the right face of a vertical plate of finite thickness. Cold fluid flowing over the right face of the plate contains a heat generation that decays exponentially with a dimensionless distance from the surface. The left face of the plate is in contact with a hot flowing fluid. The heating process on that side is characterized by a convective boundary condition that takes into account the conduction resistance of the plate as well as a possible contact resistance between the hot fluid and the left face of the plate. Using a pseudo similarity approach, the governing equations for the mixed convective flow over the right face of the plate are transformed into a set of coupled ordinary differential equations which give local similarity solutions. The effects of local Grashof numbers (defined to represent a mixed convection parameter), Prandtl number, and the internal heat generation parameter on the velocity, temperature and concentration profiles are illustrated and interpreted in physical terms.